Analysis of Metal Content of Water Well of Aek Godang Village Community Using Electrolysis Method - Matondang, Silvia Elastari (LAVOISIER: Chemistry Education Journal, 2023)
Indonesia is a country that has a good source of clean water. But do not escape from water pollution caused by population density which is increasing from day to day. This has led to an increasing consumption of water as well as consumption of water in households and in industry. The presence of metals such as Fe (iron), Al (aluminum) and Cr (chromium) in the community's water can be a concern for the health of the residents of Aek Godang and its surroundings. Under these conditions, an experiment was carried out with the aim of analyzing the content of the population's water sources (dug well water, drilled well water, river water) using TDS and water electrolyze tools. The results of this study indicate that the water sources of the Aek Godang community have TDS levels of 24 mg/L and 23 mg/L so that it can be concluded that the water sources of the Aek Godang community are in the good category.